World class and international elite athletes` and coaches` perceptions of mental demands in beach volleyball - Delviken, S.; Hofseth, E.; Riise, A. J.; Peters, D. M.; Hoigaard, R. (27th Annual Congress of the European College of Sport Science (ECSS), Sevilla, 30. Aug - 2. Sep 2022, 2022)
INTRODUCTION: In elite sport mental skills are essential for success. To develop optimal mental skills for an athlete it is essential to understand the mental demands that are critical in each sport (Taylor, 1995). Furthermore, it is essential to have knowledge about the individual athletes` exclusive needs and skills, and how they respond to the potentially unique mental demands and challenges they face in their sport. The aim of this study was to investigate how World Class and elite beach volleyball players and coaches perceive the mental demands in their sport, and how they prepare for and respond to these demands.